KEJADIAN NYERI DISMENORE PADA SANTRI PUTRI DI PONDOK PESANTREN TAHFIDZ AL MABRUR - Sherkia Ichtiarsi Prakasiwi (CV. ADIBA AISHA AMIRA, 2023)
Reproductive health is not only free from disease and disability, but also mental and social health from reproductive organs, systems, functions and processes. An understanding of dysmenorrhea is needed to be able to encourage adolescents who experience menstrual disorders or dysmenorrhea to know and take the best attitude towards reproductive problems they are experiencing, because not a few adolescents do not know about dysmenorrhea, so it will affect adolescents in carrying out their maturity. Dysmenorrhea is an imbalance of the hormone progesterone in the blood, causing pain to arise. 90% of women have experienced dysmenorrhea, this disturbs 50% of women during their reproductive years and 60-85% in their teens, which results in many absences at school or work. This study aims to determine the incidence of dysmenorrheal pain in female students at the Al-Mabrur Islamic Boarding School. This research is a type of descriptive research with a survey method. The population in this study were female students totaling 58 people. The results of the study were 3 people (5%) had no pain, 17 people (29%) had moderate pain, 35 people (60%) controlled severe pain, 3 people (5%) had uncontrolled severe pain